Vegetation and Species Diversity in a Mountain Region of Sipiso-piso, North Sumatra - Ariasta Bereona Tarigan; Delvian Delvian; T Alief Aththorick (Budapest International Research and Critics University, 2022)
The mountain region of Sipiso-piso is located adjacent to the water catchment area in Lake Toba. The region is known to have a notable uniqueness in plant species diversity from the valley to the ridge of the mountain which is only inhabited by shrubs and less stands. However, near the top of the mountain, it was characterized by a dense forest community and diverse forest vegetation with unknown information. The purpose of this study was to determine the vegetation and species diversity in the Sipiso-piso mountain region. Vegetation observation in the field used a combination method between the line transect and quadratic plots. The study documented a total of 40 plant species, with 20 families and 23 species in the forest region; 9 families and 19 species in shrubland while 2 species were recorded in both plant communities. Based on the importance value index (IVI), the forest community was evenly dominated by certain species that in shrubland. Based on the diversity index, the diversity in the forest community was classified as moderately abundant for each structure, while the shrub community was classified as moderately abundant only in the seedling but lower in the sapling, pole and tree. The evenness in the studied region was categorized as low with a distinct of species similarity among forest and shrub community.